Back Cover: Plasma Process. Polym. 9∕2014. Issue 9 (September 2014) - Rubín de Celis, David; Chen, Zhiqiang; Rahman, Md Mohklesur; Tao, Tao; McCulloch, Dougal G.; Field, Matthew R.; Lamb, Peter R.; Chen, Ying; Dai, Xiujuan J.
<x xml:space="preserve">Abstract</x> Back Cover: The combination of cold plasma with thermal treatment enables doping and changed growth of semiconductors that cannot be achieved by either treatment alone. The combination applied to commercial SnO powder produced SnO2 with a nano‐scale polycrystalline structure and controllable nitrogen doping of up to 5 at. %. This product has potential as an improved anode material for Li‐ion batteries. Further details can be found in the article Xiujuan J. Dai et al. on page 897. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>